The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1097/00000658-199911000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Standard Triple Assessment and Dynamic Magnetic Resonance Imaging of the Breast for the Evaluation of Symptomatic Breast Lesions

Abstract: ObjectiveTo compare the sensitivity and specificity of the traditional triple assessment of symptomatic breast lesions with contrast-enhanced dynamic magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 28 publications
1
14
0
3
Order By: Relevance
“…The specificity for the diagnosis of benign disease was as follows: clinical examination 83.1%, ultrasound 88.9%, mammography 86.4%, fine-needle aspiration cytology 97%, triple assessment 59.1% and MRI 90.9%. We concluded that DCE-MRI of the breast is as sensitive and more specific than the combined traditional triple assessment for the diagnosis of malignant breast lesions (Drew et al, 1999b). Similar findings have been reported in several other studies (Table 1).…”
Section: Symptomatic Diseasesupporting
confidence: 90%
“…The specificity for the diagnosis of benign disease was as follows: clinical examination 83.1%, ultrasound 88.9%, mammography 86.4%, fine-needle aspiration cytology 97%, triple assessment 59.1% and MRI 90.9%. We concluded that DCE-MRI of the breast is as sensitive and more specific than the combined traditional triple assessment for the diagnosis of malignant breast lesions (Drew et al, 1999b). Similar findings have been reported in several other studies (Table 1).…”
Section: Symptomatic Diseasesupporting
confidence: 90%
“…Imaging and pathological investigations have appreciable false negative results. When used together 95% of symptomatic breast malignancies will be diagnosed 25 …”
Section: Systematic Review Of the Literaturementioning
confidence: 99%
“…MRI provides a morphologic as well as physiologic approach to evaluating the breast. The sensitivity and specificity of MRI in detecting breast cancer ranges from 88–99% to 37–83%, respectively (3–7). While MRI has been lauded for its high sensitivity it has also been critiqued for its widely variable specificity.…”
mentioning
confidence: 99%